Proposta de interpretação para os atos elisivos: dialogando com a filosofia da linguagem e com a teoria dos sistemas - Aguiar, Tatiana (2008)
In the present work we intend to analyze the legal interpretation in the scope of the Tax law, under the approach given by the Philosophy of the Language and by the Systems Theory and still from the ideas of Paulo de Barros Carvalho, Vilém Flusser, and Niklas Luhmann, using the oportunity to appreciate, critically, the economic interpretation inside the legal universe, through some evasion acts effectively practiced by contributors. For in such a way, in a first phase, we will study the linguistic phenomenon in its general lines: its concepts, distinctions, characteristics and its relation with the reality. Later we will inside investigate the language in the comunicacional process, in order to construct the necessary premises for the analysis of the Right as product of the language. At this moment, we will have as focus of attention the exegetic activity. We will make a brief stroll on the construction of the hermeneutic theory throughout history, until arriving at the current days and our vision of the interpretation as a sense construction. We will appreciate each one of the integrant plans of the legal interpretative process and still we will face some of the profits that can surprise the interpreter to the long one to the iter hermeneutic. To finish this phase, we will present the influences of the ideas of Vilém Flusser and Luhmann on the phenomenon of the interpretation, mainly on the viability or not of the economic interpretation of the Right. In it finishes part of the work, we will try to apply all the ideas developed until then, in the analysis of the phenomenon of evasion, through the apreciation of real cases. But, before necessity becomes to trace a briefing study concerning the institute of the evasion, taking as base the native legislation on the subject, as well as the respective Brazilian and foreign doctrinal constructions